2021
DOI: 10.1051/e3sconf/202133203005
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic properties of pineapple peel juice marinated beef (Ananas comosus L. Merr)

Abstract: Beef has a high level of toughness that is not liked by consumers. The solution to increasing beef tenderness is to soften the beef. One method for tendering the beef is by marinating using local ingredients that are easily available, abundant, and inexpensive, namely pineapple. Pineapple peel is waste from pineapple that has not been utilized and is usually discarded. In pineapple peel, there is a bromelain enzyme thought to be able to hydrolyse protein so that it can tender beef. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It indicates that the immersion of meat in pineapple peel extract affects the panelists' assessment of the tenderness of Afkir layer chicken meat from very tough to very tender. The results of this study are by the research [48]. Triyono [10], in his study, reported that the higher the number obtained from measurements using a texture analyzer, the lower the softness value.…”
Section: Tendernessmentioning
confidence: 52%
“…It indicates that the immersion of meat in pineapple peel extract affects the panelists' assessment of the tenderness of Afkir layer chicken meat from very tough to very tender. The results of this study are by the research [48]. Triyono [10], in his study, reported that the higher the number obtained from measurements using a texture analyzer, the lower the softness value.…”
Section: Tendernessmentioning
confidence: 52%
“…[194] Pineapple peel Beef marination: the peel was washed, cut, mashed with a blender, and filtered; the juice was then used to marinate beef. [195] Gluten-free muffins: peels were sanitized with 100 ppm chlorinated solution for 15 min, dried for 8 h at 60 • C, and milled to obtain flour. [196] Plum peel Marmalade: peels were mixed with water and filtered to make a puree, and then sugar syrup, pectin, and citric acid were added to obtain marmalade.…”
Section: Apple Peelmentioning
confidence: 99%
“…Marination is the immersion of ingredients such as meat in a seasoned liquid solution to provide better flavour, aroma, and texture [6]. The marination process is usually done in 30 to 60 minutes, depending on the type of ingredients.…”
Section: Introductionmentioning
confidence: 99%